Knowledge and willingness towards human Papillomavirus vaccination among the parents and school teachers of eligible girls in Dhaka, Bangladesh: A school-based cross-sectional study - Samina Sultana; MD Nahid Hassan Nishan; Aklima Akter; Dalia Rahman; Fowzia Yasmin; Mohammad Delwer Hossain Hawlader (Journal of Virus Eradication)
Abstracts: Background: Cervical cancer ranks as the common prevalent cancer, among women worldwide especially impacting low-resource countries. In Bangladesh, this accounts for 12 % of all cancer cases. The development of cancer is closely linked to Human Papillomavirus (HPV) infection. Despite the availability of HPV vaccines, their uptake remains limited in Bangladesh. Thus, this research aims to assess the knowledge and willingness of parents and school teachers regarding HPV vaccination for eligible girls in Bangladesh. Methodology: This study involved 406 parents and school teachers of girls aged 9–14 years from Dhaka city. A cross-sectional study design was used. Data collection was done through a questionnaire administered by interviewers after pre-testing and refinement for clarity and reliability. Analysis was carried out using Stata 17 software. Chi-square tests and logistic regression were used to uncover associations and predictors related to knowledge levels and willingness. Results: Findings revealed that a majority of participants (64.04 %) exhibited an understanding of HPV and cervical cancer yet a high percentage (98.28 %) expressed willingness to engage in HPV vaccination initiatives. participants with primary (AOR = 3.306, p < 0.005), secondary (AOR = 8.806, p < 0.001), and higher education (AOR = 5.059, p < 0.001), as well as those from upper-middle-income groups (AOR = 3.038, p < 0.001), had significantly higher knowledge of HPV and cervical cancer. Conclusion: The research emphasizes lack of knowledge regarding HPV and its vaccination among parents and educators in Bangladesh despite a willingness to vaccinate. These results emphasize the importance of tailored initiatives and better access, to health information to increase HPV vaccine acceptance and lower the incidence of cervical cancer.